Investigation of cytotoxic, apoptosis-inducing, genotoxic and protective effects of the flavonoid rutin in HTC hepatic cells - Marcarini, Juliana Cristina; Ferreira Tsuboy, Marcela Stefanini; Luiz, Rodrigo Cabral; Ribeiro, Lucia Regina [UNESP]; Hoffmann-Campo, Clara Beatriz; Mantovani, Mario Segio (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
Rutin is a flavonoid with antioxidant, vasodilatory, anti-inflammatory and immune-stimulating activities. To study the toxicity of rutin and its protective effect, this work investigated the cytotoxic, apoptosis-inducing, genotoxic and protective effects of rutin in HTC cells. In the MTT assay, the highest concentration tested (810 mu M) showed cytotoxicity after 72 h of treatment, where cell viability and cell proliferation was diminished. None of the concentrations of rutin tested induced apoptosis after 24 h treatment. The highest concentration of rutin after 24 h treatment induced DNA damage, shown in the comet assay, but did have a genotoxic effect in the micronucleus test. Rutin was tested against the pro-carcinogenic agent benzo(a)pyrene, at concentrations of 90, 270 and 810 mu M, and was found to reduce induced DNA damage significantly. This protective effect of rutin against a pro-carcinogen, suggests an important biological activity for this compound, which can contribute to human health through the diet. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Flavonoid rutin; HTC; Cytotoxicity; Apoptosis; Protector effect